Toward quality education:a review of the academic target set for UiTMCSKS students and the contributing factors that influence it / Fatimah Bujang... [et al.] - Bujang, Fatimah (UiTM Shah Alam, Selangor, 2003)
In 2000 UiTMCSKS was awarded the ISO 9002 status for its Diploma in Civil Engineering Programme. That year the administration decided to adopt a 70% target achievement for all its Programmes. Thus far this target has not been achieved. The purpose of this study was to review if this 70% target was achievable and if it was possible, to set a time frame by which the target could be achieved. The study also sought to identify the contributing factors that determined the attainment of this target. The methodology used was the Delphi technique, which employed the expertise of the heads of Programmes and Coordinators in UiTMCSKS. The results of the study supported the contention that the 70% target set for this campus was realistic and achievable. Then, using both historical data and predicted data, an ARIMA model was employed to forecast a probable time frame to achieve this target. The model predicted that the 70% target percentage could be achieved by the year 2007. The many predictors of academic achievement are also discussed. Practical suggestions for implementation of the findings are also given together with recommendations for further research.